Determinación de Helicobacter spp. en cerdos en el departamento de Antioquia, Colombia - Rodriguez, Bernardo J.; Aranzazu, Diego; Ortiz, Laura C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Swine as well as human naturally harbor Helicobacter spp. and frequently develop gastroesophagic ulcer (GEU). Nowadays in Colombia there are no reports of natural colonization or infection by Helicobacter spp. in swine. The aim of this study investigation was to verify the presence of Helicobacter spp. in ulcerated and preulcerated lesion in the gastric mucosa of pigs and to typify to the different stages of the lesion. This research was carried out in 275 ulcerated, 15 erosioned and 15 normal stomachs obtained from Medellin abattoir at the State of Antioquia, Colombia. The analysis of the results was made by using descriptive statistic. A Z test was used to establish differences between proportions with a level of confidence of 95%. This paper report for the first time in Colombia the natural colonization of porcine stomach by Helicobacter spp. and discuss some aspects of the pathogenesis of GEU.